Thermal, physico-chemical and sensory properties of red tilapia (Oreochromis niloticus) - Ebrahimian, Mahshid (2012)
Food preservation by thermal processing is one of the common techniques to provide the market with safe products. Information about thermal properties (k, cp, ρ, α) is essential for efficient design of all food processing operation. During the chill storage of fish, many chemical and biochemical changes occur in the fish tissues, which influence quality and thermophysical properties of the stored fish. Therefore, the objectives of this study were to develop models for thermal properties of red tilapia experimentally as a function of temperature and moisture content, to find the relationship between thermal diffusivity ratio and acceptability of fish, and to investigate the effect of storage conditions (temperature, time) on texture parameters, sensory attributes, freshness and thermal properties of red tilapia. Samples were stored in chillers at 0, 4 and 8 ˚C and analyses were carried out at 0, 1, 5, 9, 13 and 17 days of storage. Full factorial design was used to arrange the possible treatments and two-way analysis of variance (ANOVA) was employed to investigate the effect of storage conditions. Thermal properties data were fitted into mathematical models and the results were compared with those reported by other researchers according to their root mean square erro (RMSE). The quality changes of fish samples were determined by K-value, sensory assessment, instrumental texture analysis and changes of thermal diffusivity ratio (α/αfresh), which included the effects of other thermal properties. The results showed that all sensory attributes (colour, odour, flavour, and general acceptability) decreased significantly (p ≤ 0.05) with increase in temperature and days of storage. A significant increase (p ≤ 0.05) in α/αfresh was obtained throughout the days of storage. There were no significant differences (p ≥ 0.05) in thermal diffusivity ratio due to changes in temperature range from 0 to 8 ˚C. The sensory evaluations were related to α/αfresh variation. There was an inverse relationship between them, and R2 for samples kept at 0, 4 and 8 ˚C were 0.84, 0.87 and 0.92, respectively. Therefore, the α/αfresh ratio can be used as a numerical tool for food technologist to measure the consumer acceptance of chilled tilapia. Textural attributes of the fish flesh (hardness, cohesiveness, adhesiveness, springiness, gumminess and chewiness) were reduced with the increase in temperature and days of storage. There was a significant decrease (p ≤ 0.05) in hardness of fish flesh during the storage period; however, no significant decreases were obtained for other texture attributes. The nucleotide degradation, as estimated by the k-value (freshness quality index) of samples stored at 0 ˚C, 4 ˚C and 8 ˚C increased significantly (p ≤ 0.05) during the storage period. The highest increase was observed for k-value of samples kept at 8 ˚C. The overall results of this study indicated that the acceptability of red tilapia was 17 days at 0 ˚C, 9 days at 4 ˚C and 5 days at 8 ˚C by sensory and k-value methods. However, the suitability of thermal diffusivity ratio to assess freshness need to be more thoroughly researched.